An experimental investigation on the effect of ferrofluids on the efficiency of novel parabolic trough solar collector under laminar flow conditions - Alsaady, Mustafa; Fu, Rong; Liu, Zeyu; Yan, Yuying; Wu, Shenyi; Boukhanouf, Rabah (Taylor & Francis, 2018)
The paper is related to the use of magnetic nanofluids (ferrofluids) in a direct absorption solar parabolic trough collectors enhances thermal efficiency compared to conventional solar collectors. By applying the right magnetic intensity and magnetic field direction, the thermal conductivity of the fluid increased higher than typical nanofluids. Moreover, the ferrofluids exhibit excellent optical properties. The external magnetic source is installed to alter the thermos-physical properties of the fluid, and the absorber tube does not have selective surface allowing ferrofluids to absorb the incoming solar irradiance directly. In this paper, an experimental investigation of the performance of direct absorption solar collector using ferrofluids as an absorber. Various nanoparticle concentrations 0% to 1vol% at the operational temperatures between 19°C and 40°C were used in the current study. The results show that using ferrofluids as a heat transfer fluid increases the efficiency of solar collectors. In the presence of the external magnetic field, the solar collector efficiency increases to the maximum, 25% higher than the conventional parabolic trough. At higher temperatures, the ferrofluids show much better efficiency than conventional heat transfer fluid. The study indicated that nanofluids, even of low-content, have good absorption of solar radiation, and can improve the outlet temperatures and system efficiencies.